2021
DOI: 10.18632/aging.202571
|View full text |Cite
|
Sign up to set email alerts
|

Elevated frequencies of CD14+HLA-DRlo/neg MDSCs in COVID-19 patients

Abstract: Background: The immune responses, hyper-inflammation or immunosuppression, may be closely related to COVID-19 progression. We aimed to evaluate the changes of frequency of CD14 + HLA-DR lo/neg MDSCs, a population of cells with potent immunosuppressive capacity, in COVID-19 patients. Methods: The levels of CD14 + HLA-DR lo/neg MDSCs were determined by flow cytometry in 27 COVID-19 patients, and their associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) global pandemic can cause severe pneumonia, which manifests hyperinflammation and immunosuppression ( 29 ). MDSCs were found to expand in the patients infected with SARS-CoV-2, and the frequency of MDSCs was correlated with COVID-19 disease severity ( 18 , 19 ). Therefore, the frequency of MDSCs was suggested as a predictor of COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel coronavirus severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) global pandemic can cause severe pneumonia, which manifests hyperinflammation and immunosuppression ( 29 ). MDSCs were found to expand in the patients infected with SARS-CoV-2, and the frequency of MDSCs was correlated with COVID-19 disease severity ( 18 , 19 ). Therefore, the frequency of MDSCs was suggested as a predictor of COVID-19 severity.…”
Section: Discussionmentioning
confidence: 99%
“…Two major subsets of MDSCs in humans have been identified: CD11b + CD14 − CD15 + granulocytic-MDSCs (G-MDSCs) or polymorphonuclear-MDSCs (PMN-MDSCs) with a low density, and CD11b + CD14 + HLA-DR low/− CD15 − monocytic-MDSCs (M-MDSCs) (16). Previously, the expansion of MDSCs has been reported in patients with sepsis or coronavirus disease 2019 (COVID-19), and it was correlated with the severity of the diseases (17)(18)(19). Our previous work also found a lower expression of HLA-DR on monocytes in KTRs with pneumonia, indicating the possibility of MDSC expansion in these patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…The literature is inconclusive regarding the correlation between the number of MDSCs and immunological parameters in COVID-19 patients. Several studies reported negative correlations between the frequencies of MDSCs and the absolute counts of T cells in COVID-19 patients [ 68 , 75 , 85 , 86 ]. There was also a negative correlation between the number of M-MDSCs and activated CD8 + T cells [ 73 ].…”
Section: Mdscs In Covid-19mentioning
confidence: 99%
“…Some studies reported a negative correlation between MDSC frequencies and NK cells in COVID-19 patients, suggesting that MDSCs may be involved in the inhibition of this innate immune cell population in COVID-19 [ 85 , 86 ]. Two studies investigated correlations between MDSCs and inflammatory markers in patients with COVID-19.…”
Section: Mdscs In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation